Mapping of Agricultural Land Use Change and Effect on Land Capability as a Basis for Land Use Direction in Nguntoronadi-Indonesia - Mujiyo Mujiyo; Suntoro Suntoro; Rifa Rizhandion Akbar; Rahayu Rahayu (International Journal of Agriculture System, 2022)
The occurrence of conversion of agricultural land can cause erosion proneness, low fertility soils, and decreased land productivity. Land conversion requires an evaluation of land capability, as a basis for direction to maintain land productivity. This study aims to determine the rate of conversion of agricultural land, land capability class, the determinants of land capability, and direction of land management on initial land and converted land in agricultural land, Nguntoronadi District, Karanganyar Regency. The method used is a survey, with the research area divided into 6 LMU (Land Map Units) represented by 6 sample points in each LMU including 3 points on fixed land and 3 points on converted land, resulting in 36 samples determined by purposive sampling. The research stages include; 1) Pre survey, 2) Survey, 3) Post survey. The results of the study show that the land-use change from 2011 to 2020 covers an area of 258.56 ha and a rate of 28.73 ha per year. The land capability of the research area on fixed land and converted land is classified into land capability III and class IV. Factors that determine land capability include soil erodibility and drainage. The recommended direction for land use and management for Nguntoronadi District is the provision of green manure, making terracing, and making drainage irrigation